Expert Panel Recommendations for Use of Standardized Glucose Reporting System Based on Standardized Glucometrics Plus Visual Ambulatory Glucose Profile (AGP) Data in Clinical Practice - Dagdelen, Selcuk; Deyneli, Oguzhan; Dinccag, Nevin; Ilkova, Hasan; Osar Siva, Zeynep; Yetkin, Ilhan; Yilmaz, Temel (Frontiers in Endocrinology, 2022)
This expert panel of diabetes specialists aimed to provide guidance to healthcare providers on best practice in use of innovative continuous glucose monitoring (CGM) techniques through a practical and implementable document that specifically addresses the rationale for as well as analysis and interpretation of the new standardized glucose reporting system based on standardized CGM metrics and visual ambulatory glucose profile (AGP) data. This guidance document presents recommendations and a useful algorithm for the use of standardized glucose reporting system in the routine diabetes care setting